Development of ethnopedagogical augmented reality media “culture spinner” for elementary cultural diversity - Novi Setyoningsih; Muhamad Afandi (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
Pancasila Education learning on the topic of cultural diversity in elementary schools still faces challenges in enhancing students’ understanding of local culture engagingly and contextually. This study aimed to develop and examine the feasibility, practicality, and effectiveness of an Augmented Reality-based culture spinner media for elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included media experts, material experts, language experts, classroom teachers, and 28 elementary school students. Data collection instruments consisted of expert validation questionnaires, teacher and student response questionnaires, and learning achievement tests administered through pretests and posttests. The results showed that the developed learning media achieved a “highly feasible” category from media experts with a percentage of 93.18%, material experts with 88.16%, and language experts with 92.11%. Teacher assessments also indicated a “highly feasible” category with a percentage of 100%, while student responses demonstrated a “very practical” category with a percentage of 100%. The effectiveness test revealed an improvement in students’ learning outcomes, with the average pretest score increasing from 60.71 to a posttest score of 83.14. The N-Gain analysis yielded a score of 0.57, which falls into the moderate category. Therefore, the culture spinner media was declared feasible, practical, and effective for supporting Pancasila Education learning on the topic of cultural diversity in elementary schools.